Bilateral Hip Joint Hylan G-F 20 Granulomatous Synovitis due to Viscosupplementation Injections. (25th August 2014) - Weinrauch, Patrick; Trigger, Robert; Tsikleas, George
Abstract : We present the diagnosis of bilateral granulomatous inflammation of the hip joints associated with Hylan G-F 20 viscosupplementation injections. Clinicians recommending therapeutic Hylan injections for the management of hip arthritis should maintain clinical awareness regarding this potential complication.